Development of E-Book Biology Question Bank Model for Minimum Competency Assesment To Train Information Literacy (FMIPA UNNES, 2023)
The question bank developed in this study contains biology questions on the Minimum Competency Assessment (AKM) Level 5 Class 10 model to train students' information literacy. This question bank is intended to train students' literacy and familiarize students with AKM questions. A question bank contains a set of items that are calibrated for validity, item difficulty and reliability. The purpose of this research is to create a question bank based on validity proof, analysis of item difficulty levels and estimating the reliability of AKM model biology questions. This research uses the ADDIE model with the stages of analysis, design, development, implementation and evaluation. The feasibility of AKM model biology questions that will be tested is validated by material experts. Item analysis uses the Rasch 1PL model approach with the Winstep application. The results of the study showed that the AKM biology questions were declared feasible by experts and 48 items were valid, 7 items were very easy, 18 items were easy, 17 items were difficult, 8 items were very difficult, and the reliability value was in the excellent category. The conclusion of this question bank is that 34 items are included in the question bank and 16 other items are not included.